Biological Codes and Topological Causation. - Jantzen, Benjamin; Danks, David (Philosophy of Science, 2008)
Various causal details of the genetic process of translation have been singled out to account for its privileged status as a 'code'. We explicate the biological uses of coding talk by characterizing a class of special causal processes in which topological properties are the causally relevant ones. This class contains both the process of translation and communication theoretic coding processes as special cases. We propose a formalism in terms of graphs for expressing our theory of biological codes and discuss its utility in understanding biological systems.